The Relationship Between the Functional Gait Assessment and Quality-of-Life Data in Patients Undergoing Vestibular Schwannoma Resection. Issue 7 (August 2021) - Said, Mena; Lee, Jason; Moshtaghi, Omid; Saliba, Joe; Richardson, Alexander J.W.; Ngo, Victoria; Mehranpour, Pasha; Schwartz, Marc S.; Friedman, Rick A.
Abstract : Objective: To examine the relationship between the Functional Gait Assessment (FGA) and quality of life (QOL) measurements relating to balance before and after vestibular schwannoma (VS) resection and to assess the role of preoperative FGA in predicting postoperative QOL. Study Design: A prospective clinical study of adult patients undergoing VS resection between September 2018 and December 2019. FGA was administered 1 week before and after surgery. Dizziness Handicap Inventory (DHI) and Penn Acoustic Neuroma Quality of Life (PANQOL) were administered preoperatively and at 3 months postoperatively. Setting: Single tertiary center. Patients: Patients (age ≥ 18 years old) with VS undergoing microsurgical resection. Excluded were patient with previous surgery or radiation. Intervention: VS resection. Main Outcomes and Measures: Primary outcome: correlation between FGA and QOL surveys. Secondary outcome: correlation between preoperative measurements of balance and postoperative PANQOL. Results: One hundred thirty-eight patients were analyzed (mean age: 48 years old, 65.9% female). The translabyrinthine approach was most commonly performed. Under multivariate analysis, preoperative FGA significantly correlated with preoperative PANQOL balance score ( p  < 0.0001), preoperative PANQOL total score ( p  = 0.0002), and preoperative DHI ( p  < 0.0001). However, postoperative FGA did not significantly correlate with postoperative PANQOL balance or total scores ( p  = 0.446 and p  = 0.4, respectively), or postoperative DHI ( p  = 0.3). Univariate analysis demonstrated that preoperative DHI and preoperative FGA were predictive of changes in postoperative PANQOL balance and total scores. However under multivariate analysis, preoperative FGA did not predict changes in postoperative PANQOL balance or total score ( p  = 0.24; p  = 0.28, respectively). Preoperative DHI remained predictive of changes in postoperative PANQOL balance ( p  = 0.03) score but not of postoperative PANQOL total score ( p  = 0.37). Conclusions: Although FGA and QOL data significantly correlated in the preoperative setting, our results did not suggest that preoperative FGA can be used to determine postoperative QOL. Additionally, the lack of correlation between FGA and QOL measurements in the acute postoperative setting suggests that further research is needed to determine contributors to postoperative QOL.